Documents on the laws of war - Roberts, Adam, 1940-; Guelff, Richard, 1950- (Oxford : Clarendon Press ; New York : Oxford University Press, 1989)
This concise reference work has been extensively revised and updated. It has been prepared with the assistance of the official Depositaries of the various international agreements and will be of use to statesmen and diplomats, lawyers, journalists and students of international relations.
1856 Paris Declaration respecting maritime law; 1868 St Petersburg declaration renouncing the use, in time of war, of explosive projectiles under 400 grammes weight; 1899 Hague Declaration II concerning asphyxiating gases; 1899 Hague Declaration III concerning expanding bullets; 1907 Hague Convention IV respecting the laws and customs of war on land; 1907 Hague Convention V respecting the rights and duties of neutral powers and persons in case of war on land; 1907 Hague Convention VI relating to the status of enemy merchant ships at the outbreak of hostility; 1907 Hague Convention VII relating to the conversion of merchant ships into warships; 1907 Hague Convention VIII relative to the laying of automatic submarine contact mines; 1907 Hague Convention XI relative to certain restrictions with regard to the exercise of the right of capture in naval war; 1907 Hague Convention XIII concerning the rights and duties of neutral powers in naval war; 1923 Hague rules of aerial warfare; 1925 Geneva protocol for the prohibition of the use in war of asphyxiating, poisonous or other gases, and of bacteriological methods of warfare; 1936 London proces-verbal relating to the rules of submarine warfare set forth in part IV of the Treaty of London of 22nd April 1930; 1946 judgement of the International Military Tribunal at Nuremberg - extracts on crimes against international law; 1948 United Nations convention on the prevention and punishment of the crime of genocide; 1949 Geneva Convention I for the amelioration of the condition of the wounded and sick in armed forces in the field; 1949 Geneva Convention II for the amelioration of the condition of wounded, sick and shipwrecked members of armed forces at sea; 1949 Geneva Convention III relative to the treatment of prisoners of war; 1949 Geneva Convention IV relative to the protection of civilian persons in time of war; 1954 Hague protocol for the protection of cultural property in the event of armed conflict; 1971 Zagreb Resolution of the Institute of International Law on conditions of application of humanitarian rules of armed conflict to hostilities in which United Nations forces may be engaged; 1977 United Nations Convention on the prohibition of military or any other hostile use of environmental modification techniques; 1977 Geneva Protocol I and II additional to the Geneva Conventions of 12th August 1949, and relating to the protection of victims of non-international armed conflicts; 1978 Red Cross fundamental rules of international humanitarian law applicable in armed conflicts; 1981 United Nations Convention on prohibitions or restrictions on the use of certain conventional weapons which may be deemed to be excessively injurious or to have indiscriminate effects. Appendix: emblems and signs.
Includes index.
Bibliography: p. 491-497.
Keywords: War (International law)